Análise comparativa entre as propriedades mecânicas de concretos produzidos com brita granítica e com seixo rolado para uma mesma faixa de resistência à compressão - Barbalho, Anne Priscila de Castro Bezerra (Universidade Federal Rural do Semi-Árido, 2017)
How there is a big demand of concrete by the current market and a lot of very old reinforced concrete structures, it becomes important and necessary a comparative evaluation between the properties of the conventional concrete, produced with granite gravel, more used in Brazil today, and of the concrete produced with rolled pebbles, concrete used in long-standing structures. So, cylindrical specimens were produced with both types of concrete and subjected to tests of resistance to axial compression, ultrasonic pulse velocity, absorption and porosity, in addition to prismatic blocks also produced with both types of concrete and submitted to the ultrasonic pulse velocity and sclerometry assay. With the obtained results, it was verified that the resistance values obtained by the test of resistance to the axial compression were below the expected one, being around 50% greater for the concrete with granite gravel. The concrete produced with rolled pebbles had lower rates of absorption and porosity compared to concrete with granite gravel. In addition, through the ultrasound and sclerometry tests, the concretes produced were classified as homogeneous and of good quality.
Monografia
Keywords: Concreto endurecido; Concreto fresco; Qualidade do concreto; Relação água/cimento; Agregado graúdo; ENGENHARIAS::ENGENHARIA CIVIL